Stabilisation policies to strengthen Euro area resilience - Stráský, Jan (OECD Publishing, 2018)
The euro area sovereign debt crisis highlighted important weaknesses in the euro area design. Fiscal policy did not build sufficient buffers before the crisis, which forced some countries to tighten fiscal policy too rapidly during the downturn to restore market confidence in sovereign borrowing. Despite this, sovereign stress remained high, weakening further the banking sectors highly exposed to government bonds, which in return reduced further market confidence in fiscal sustainability in case of banks' bailout. As a result, monetary policy was the main public instrument to support the activity, but its effectiveness was reduced by the fragmentation of financial markets along national lines as the crisis deepened. In order to durably sever the links between banks and their sovereigns, euro area countries agreed on a banking union. The creation of a common supervisor was a very important step in that direction.
Keywords: Economics; Euro Area